Piezostrain tuning exchange bias mediated by electric field in composite heterostructure. (8th November 2017) - Li, Pingping; Zhou, Cai; Wang, Wenqiang; Cao, Cuimei; Yao, Jinli; Jiang, Changjun
Abstract: The change of unidirectional anisotropy and uniaxial anisotropy field turned by piezostrain in an IrMn/Co/Ta/Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 heterostructure with an exchange bias was investigated by ferromagnetic resonance at room temperature. The curve of the magnetic resonance field versus the electric fields showed an asymmetric butterfly-like behavior, which was consistent with the result of strain versus electric field curves. This butterfly-like behavior can be attributed to the piezostrain effect. Specifically, the non-volatile uniaxial anisotropy field and unidirectional anisotropy field behavior under different electric fields induced by piezostrain effect were obtained. Our result is crucial for further application of future multiferroic devices.